Awareness Regarding Cancer Risk Factors among Udayapur Cement Factory, Eastern Nepal - Koirala, Sushila; Baral, Prava; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2025)
Background: Cancer continuous to be a major cause of morbidity and mortality throughout the world including Nepal. It is estimated 19.3 million new cases were diagnosed, accounting for 9.9 million death cases in 2020. Cancer risk factors are the things that can increase a person’s chances of developing cancer. Methods: A quantitative cross-sectional study design on “Awareness Regarding Cancer Risk Factors among Udayapur Cement Factory workers” was carried out to assess the level of awareness regarding cancer risk factors. Purposive sampling technique was used to select the sample and the sample size was 93. Data was collected by using structured interview schedule. Both descriptive and inferential statistics were used for data analysis with SPSS version 20. Results: The Mean age of respondents was 41.89 years with minimum age of 20 years and maximum age of 58 years and all the respondents were male. Most of the respondents were Hindu (94.6%) and less than half (44.1%) of respondents were Brahmin/Chhetri. The study findings summarized the level of awareness into three categories where 80.6% had poor level of awareness, 18.3% had moderate level of awareness and 1.1% had good level of awareness. Conclusion: Majority of the respondents had poor level of awareness of cancer risk factors. So, awareness programs regarding cancer prevention should be planned and implemented from the concern authority targeting the cement factory workers so that morbidity and mortality due to cancer can be reduced to some extent by increasing their level of and awareness on cancer.